2006
DOI: 10.1007/s10549-006-9396-4
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear morphometric features in benign breast tissue and risk of subsequent breast cancer

Abstract: Certain nuclear morphometric features measured in breast tumor tissue have been shown to predict the prognosis of breast cancer patients. However, the application of these features to predicting risk of breast cancer development has received little attention. We conducted a case-control study to evaluate nuclear morphometric features in benign breast tissue in association with subsequent breast cancer risk. The study was nested within a cohort of 4,888 women with a histopathologic diagnosis of benign breast di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…These results are in agreement with multiple studies that have shown the prognostic significance of nuclear morphometry in female and male breast cancer patients. [2][3][4][5][6][7][8] Altogether, this suggest that prognostication in male breast cancer could benefit from replacing classical nuclear atypia scoring according to the Bloom and Richardson grading system by automated nuclear morphometry of whole slide images.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results are in agreement with multiple studies that have shown the prognostic significance of nuclear morphometry in female and male breast cancer patients. [2][3][4][5][6][7][8] Altogether, this suggest that prognostication in male breast cancer could benefit from replacing classical nuclear atypia scoring according to the Bloom and Richardson grading system by automated nuclear morphometry of whole slide images.…”
Section: Discussionmentioning
confidence: 98%
“…The usefulness of nuclear morphometry by image analysis in providing more objective and reproducible prognosis for breast cancer patients has been recognized for a long time. [2][3][4][5][6][7][8] Prognostically important features express the nuclear size and shape (and in some cases the nuclear texture and the architecture of the tissue 9 ) in a quantitative manner. Incorporating nuclear morphometry features into grading would therefore make sense, but wider acceptance of such an approach to histological grading has been hampered by the tedious and time consuming nature of the manual segmentation of nuclei.…”
mentioning
confidence: 99%
“…Some of the breast studies have also measured long axis and short axis as nuclear morphometric parameters, but among the nuclear parameters nuclear area and perimeter are important [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…A smaller aspect ratio indicates a flatter contour. Definition of particle shape is a long-standing problem and there is no standard definition (Carter and Yan, 2005;Cui et al, 2007). The formula of shape factor (SF) used in this study's imaging based system is defined as:…”
Section: Quantitification Proceduresmentioning
confidence: 99%